Cross sectional survey of maternal and newborn quality of care in Niger: Selected findings, lessons learned and recommendations. - Alexandre Quach; Barbara Madaj; Katie Fahy; Aminata Tinni Konate; Ibrahim Souley; Lucien Omar Marcel; Adama Traore; Monir Islam; Uzochukwu Egere; Charles Anawo Ameh (PLOS Global Public Health)
Comprehensive assessments of quality of care (QoC) are essential for monitoring progress towards meeting global and national maternal and newborn health (MNH) targets. Liverpool School of Tropical Medicine (LSTM) and the Niger Ministry of Public Health adapted a 2014 WHO QoC tool to cover antenatal care (ANC) and postnatal care (PNC) and include client voices through exit interviews. The objectives of the study were to assess quality of MNH care in Niger and to document lessons learnt from implementing the LSTM QoC tool. Quality of Care (QoC) was assessed using five tools: health facility survey (using register and official record data), partograph reviews, healthcare provider knowledge assessment, exit interviews with clients, and observation of antenatal and postnatal care. A nationally representative sample of 110 public healthcare facilities at three levels (integrated health centres, district hospitals and mother-child hospitals) and 2153 women were included. Descriptive analysis with 95% confidence intervals was presented. The health facility survey showed variable access to electricity (63% [53-72]), water (72% [62-81]), and transportation (40% [31-50]). Tests and treatment for HIV, TB, and malaria were found in more than 90% of relevant facilities. During observation of first ANC visit, 62% [48-74] women were tested for HIV; 13% [5-30] for pre-eclampsia and 22% [12-36] for anaemia. Observation of PNC showed much lower rates of screening (15% [7-27] tested for HIV and 4% [0;11] for malaria). Partographs were used in 86% of deliveries with inconsistent completion. At client interviews, respectful care indicators were variable, with providers not always explaining results to clients (59% [50-67]). Targeted allocation of resources and training could impact on QoC and reduce missed opportunities for prevention, screening and management of diseases among pregnant women and babies. The QoC assessment tool proved capable of offering a comprehensive overview of priorities in MNH, while maintaining feasibility in the Nigerien context.